2021
DOI: 10.2196/24180
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Sensing Apps and Self-management of Mental Health During the COVID-19 Pandemic: Web-Based Survey

Abstract: Background During the COVID-19 pandemic, people had to adapt their daily life routines to the currently implemented public health measures, which is likely to have resulted in a lack of in-person social interactions, physical activity, or sleep. Such changes can have a significant impact on mental health. Mobile sensing apps can passively record the daily life routines of people, thus making them aware of maladaptive behavioral adjustments to the pandemic. Objective Thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Since the onset of the novel coronavirus disease (COVID-19) outbreak in the United States, the established concern for college and post-graduate student mental health is being increasingly explored and reviewed [ 2 ]. The rapid progression and spread of COVID-19 within the country had disturbed and displaced students from their classrooms and forced them to abruptly adapt from in-person learning to a virtual environment [ 3 ]. Education has been delivered through different online modalities prior to the pandemic; however, students were required to transition to an online learning-only environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the onset of the novel coronavirus disease (COVID-19) outbreak in the United States, the established concern for college and post-graduate student mental health is being increasingly explored and reviewed [ 2 ]. The rapid progression and spread of COVID-19 within the country had disturbed and displaced students from their classrooms and forced them to abruptly adapt from in-person learning to a virtual environment [ 3 ]. Education has been delivered through different online modalities prior to the pandemic; however, students were required to transition to an online learning-only environment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a study with 741 student participants found that despite low usage or no history of using a mental health app, students were overall interested in immediate access to mental health assistance [ 9 ]. Within a sample of 474 participants, one study determined that 66% of individuals believed a mobile application during the COVID-19 pandemic was significantly helpful, especially in those with a history of mental disorders [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high level of contagion of the disease, since the first cases appeared in the country, the Portuguese authorities took measures to restrict movement and implement social isolation, the first lockdown being decreed on March 18, 2020 [2]. By suddenly adapting their lives to the sanitary measures implemented by the government, people had to adapt to a new reality with fewer social interactions, physical activity, and sleep [3]. These new rules changed everyday life as a whole.…”
Section: Introductionmentioning
confidence: 99%